Algebra Help?

Follow
  • Follow publicly
  • Follow privately
  • Unfollow
Perform the indicated operations and simplify: (2y)2 (2y3) x2 + 13x +40 = 0 3x3 – 588x = 0 x2 + 2x = 63 49p2 – 112p + 64 = 0 ...show more
Best AnswerAsker's Choice
1)
(2y)2 (2y3)
= 4y(2y^3)
= 8y^4

2)
x2 + 13x +40 = 0
x^2 + 5x + 8x + 40 = 0
x(x + 5) + 8(x + 5) = 0
(x + 8)(x + 5) = 0
x = -8
or
x = -5

3)
3x^3 – 588x = 0
3x(x^2 - 196) = 0
3x(x-14)(x+14) = 0
x = 0
or
x = 14
or
x = -14

4)
x^2 + 2x = 63
x^2 + 2x - 63 = 0
x^2 - 7x + 9x - 63 = 0
x(x-7) + 9(x-7) = 0
(x + 9)(x - 7) = 0
x = -9
or
x = 7

5)
49p2 – 112p + 64 = 0
(7p)^2 - 2(7p)(8) + (8)^2 = 0
(7p - 8)^2 = 0
p = 8/7

6)
21y2 + y – 2
=21y^2 - 7y + 6y - 2
=7y(3y - 1) + 2(3y - 1)
= (7y + 2)(3y - 1)

Asker's rating & comment

5 out of 5
THANK YOU
  • Rate
  • Comment

Other Answers (7)

Rated Highest
  • Rated Highest
  • Oldest
  • Newest
  • ironduke8159 answered 7 years ago
    (2y)2 (2y3) =4y^5

    x2 + 13x +40 = 0
    (x+8)(x+5) =0 --> x = -5 or -8

    3x3 – 588x = 0
    3x(x^2-196) = 0 --> x=0 or -14 or +14

    x2 + 2x = 63
    (x+9)(x-7) = 0 ==> x = -9 or 7

    49p2 – 112p + 64 = 0
    (7p-8)^2 = 0
    7p-8 = 0 --> p = 8/7

    Factor this trinomial completely: 21y2 + y – 2
    (3y+1)(7y-2)
    • Rate
    • Comment
  • mohanrao d answered 7 years ago
    1)
    8y^5
    2)
    (x + 5)(x + 8) = 0
    x =-5 or -8
    3)
    3x(x^2 - 196) = 0
    3x(x + 14)(x - 14) = 0
    x = 0, 14 , -14
    4)
    x^2 + 2x - 63 = 0
    (x + 9)(x - 7) =0
    x = -9 or 7
    5)
    49p^2 - 112p + 64 =0
    (7p - 8)^2 = 0
    p = 8/7
    6)
    21y^2 + 7y - 6y -2 =0
    7y(3y + 1) -2(3y + 1) =0
    (3y + 1)(7y - 2) =0
    y = -1/3 or 2/7
    • Rate
    • Comment
  • erikzarikian answered 7 years ago
    1) Not sure if those are exponents or not...
    If it is (2y)^2 * 2y^3, then the answer is 8y^5
    2) (x+5)(x+8)
    x = -5, -8

    3) 3x ( x^2 - 196) <-- factoring out the 3x
    3x ( x - 14) ( x+14) <-- difference of squares
    x = 0, 14, -14

    4. x^2 + 2x - 63 = 0
    (x-7)(x+9)
    x=7, -9

    5. (7p-8)(7p-8) or (7p-8)^2

    p = 8/7

    6. (7y-2)(3y+1)

    Source(s):

    Myself
    • Rate
    • Comment
  • Palatino answered 7 years ago
    1) (2y)2(2y3) = 96*4y
    I'll use commutative and distributive property
    2(2y)(2y*3)
    2(2)*2y*2(2)*2y*2(3)
    4*2y*4*2y*6
    Multiply variables with variables and normal numbers with normal numbers.
    4*4*6*2y*2y
    96*4y

    2) x2 + 13x +40 = 0
    2x + 13x + 40 = 0
    15x + 40 = 0
    15x = 0 - 40
    15x = -40
    x= -40/15 = -2.6

    3) Couldn't do it, sorry =S

    4) x2 + 2x = 63
    2x + 2x = 63
    4x = 63
    x = 63/4 = 15.75

    5) Couldn't do it =/
    • Rate
    • Comment
  • Pri_Rox answered 7 years ago
    x2+13x+40 = (x+5)(X+8) X= -5,-8

    3x3-588x=0 equals 3x(x2-196) so x= 0,14,-14

    x2+2x=63 equals (x-7)(x+9) x= 7, -9

    49p2-112p+64 is (7p-8) squared p=8/7

    trinomial = (3y+1) (7y-2) y= -1/3, 2/7
    • Rate
    • Comment
  • davidosterberg1 answered 7 years ago
    8y^5
    (x+8)(x+5)=0 x=-8, x=-5
    3x(x^2-196)=0 x=0, x= +/- 14
    (x+9)(x-7)=0 x=-9, x=7
    (7p -8)(7p-8) p=8/7
    (7y-2)(3y+1)
    • Rate
    • Comment
  • readingnut210 answered 7 years ago
    2y5

    (x+5)(x+8)=0 (x=-5, -8)

    (3x + 42)(x - 14) = 0, x= 14

    x2 + 2x - 63 = 0, (x+9)(x-7) = 0, x = -9, 7

    (7p + 8)(7p + 8) = 0, x= -8/7

    (3y+1)(7y-2)
    • Rate
    • Comment
  • Sign In 

    to add your answer

Who is following this question?

    %
    BEST ANSWERS
    Member Since:
    Points: Points: Level
    Total Answers:
    Points this week:
    Follow
     
    Unfollow
     
    Block
     
    Unblock